Ethnobotanical Study of Tamarind (Tamarindus indica L.) in Lebakrejo Village, Purwodadi District, Pasuruan Regency - Siti Salma Nur Fahima; Ari Hayati; Hasan Zayadi (Berkala Ilmiah Biologi, 2022)
Tamarind (Tamarindus indica L.) is a plant that has many benefits ranging from leaves, stems, fruit to seeds. This study aims to evaluate the public's perception of aspects of the utilization and alanyze the distribution of tamarind in Lebakrejo Village, Purwodadi District, Pasuruan Regency. This research uses descriptive exploratory methods include: literature study, observations, interviews using questionnaires, and data analysis. The results of this study indicate that the perception of the people of Lebakrejo Village, Purwodadi District, Pasuruan Regency using tamarind in various daily needs, including herbal medicine, food ingredients, fuel, tools, animal feed, medicine, sources of income, culture, cultivation, and land boundaries. The distribution of tamarind in Lebakrejo village based on land use is distributed in the houseyard, farmland, and roadside with each frequency is 100%.